2020
DOI: 10.1021/acsabm.0c00698
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Municipal Biowaste into Electrospun Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) Biopapers for Food Packaging Applications

Abstract: The present study reports on the production and characterization of a new biopackaging material made of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) derived from municipal biowaste (MBW) and produced by the mixed bacterial culture technology. After purification and extraction, the MBW-derived PHBV was processed by electrospinning to yield defect-free ultrathin fibers, which were thermally post-treated. Annealing at 130 °C, well below the biopolymer's melting temperature (Tm), successfully yielded a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 69 publications
1
45
1
Order By: Relevance
“…Many FTIR bands in polymers are conformationally sensitive, being the sharper peaks associated to ordered chain segments along the backbone, arising mostly from within crystals. When the relative intensity of conformationally sensitive bands rises upon heating, they typically sharpen, shifting in position and become narrower [ 57 ]. From Figure 8 , a progressive increase in the intensity of many bands was initially observed, associated to classical crystal perfecting, followed by a leveling-off of these and a subsequent decrease up to around 160 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many FTIR bands in polymers are conformationally sensitive, being the sharper peaks associated to ordered chain segments along the backbone, arising mostly from within crystals. When the relative intensity of conformationally sensitive bands rises upon heating, they typically sharpen, shifting in position and become narrower [ 57 ]. From Figure 8 , a progressive increase in the intensity of many bands was initially observed, associated to classical crystal perfecting, followed by a leveling-off of these and a subsequent decrease up to around 160 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the electrospun mats can be, thereafter, post-treated at temperatures below the T m of the polymer, forming fiber-based continuous films with eliminated porosity. These materials are also called “biopapers” when made of biopolymers [ 56 , 57 ] due to their biofiber-based morphology and improved properties compared to traditional cellulosic papers. Thus, these materials can be produced after using minimal thermal exposure and they show good optical as well as mechanical and barrier properties, potentially offering high value in food packaging applications [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary results showed that it is possible to obtain biodegradable films (for agricultural purposes) with acceptable mechanical and permeability properties through melt compounding and blown extrusion, starting from mixtures at different PHA content. Also packaging applications have been explored by Melendez-Rodriguez et al (2020) on PHA from Treviso, carrying out a wide characterization on fiber-based continuous films obtained starting from electrospun PHA. The combination of electrospinning and a mild annealing postprocessing below the biopolymer’s T m was able to yield unique biomaterials with balanced mechanical, thermal and barrier properties ( Melendez-Rodriguez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also packaging applications have been explored by Melendez-Rodriguez et al (2020) on PHA from Treviso, carrying out a wide characterization on fiber-based continuous films obtained starting from electrospun PHA. The combination of electrospinning and a mild annealing postprocessing below the biopolymer’s T m was able to yield unique biomaterials with balanced mechanical, thermal and barrier properties ( Melendez-Rodriguez et al, 2020 ). Furthermore, one of the main concerns relating to the use of waste as feedstock is the content of pollutants that can migrate from the waste, through the technology chain, and into the end-products.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Cherpinski et al [42] developed multilayer films based on PHB nanopapers, showing that the multilayers presented a similar continuous structure and strong interlayer adhesion, which was attributed to the coalescence process at the fiber interphase. This annealing process, performed at temperatures well below the polymer's melting point, has been recently described and better understood by Melendez-Rodriguez et al [43] Nanomaterials 2020, 10, x FOR PEER REVIEW 10 of 24…”
Section: Morphologymentioning
confidence: 95%